Determination of clinical efficiency of pediatric rotary file systems for root canal preparation in primary molars - A comparative study - K L Girish Babu; G Kavyashree; Geeta Maruti Doddamani (Wolters Kluwer Medknow Publications, 2022)
Introduction: To meet the demand of pediatric endodontists, exclusive pediatric rotary file systems have been recently introduced by the manufactures. However, no study has been conducted to compare the clinical efficiency between pediatric rotary file systems. Aim: To determine the clinical efficiency (instrumentation time, obturation time, quality of obturation and postoperative pain) of two pediatric rotary file systems following the root canal preparation of primary molars. Materials and Methods: A total of 75 primary molars requiring pulpectomy were selected from children aged 4 to 7 years. These teeth were divided into three groups of 25 teeth each. In the first, second, and third groups, the cleaning and shaping of the root canals were carried out with Pedo-Flex pediatric rotary files (Group PF), Kedo-S pediatric rotary files (Group KS), and, manual nickel-titanium K-files (Group MF), respectively. Obturation was carried out with zinc oxide eugenol cement with an engine-driven Lentulo spiral. The instrumentation and obturation times were recorded. The quality of the root filling was radiographically assessed immediately after obturation. The postoperative pain was evaluated at time intervals of 6, 12, 24, 48, 72 h, and 1 week. Results and Discussion: The instrumentation and obturation times were significantly less with the use of pediatric rotary file systems compared to the manual file system. The quality of obturation was superior in the root canals instrumented with pediatric rotary file systems compared to manual files. There was decreased postoperative pain with the use of pediatric rotary file systems as compared to manual files. In all three groups, postoperative pain decreased over time. The optimally filled root canals showed a significant correlation with the absence of postoperative pain. Conclusions: The use of pediatric rotary file systems for root canal instrumentation of primary molars resulted in the superior quality of obturation in decreased instrumentation and obturating times with the least postoperative pain. The overfilled root canals were not associated with significant postoperative pain.